2021
DOI: 10.31219/osf.io/td4cs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highlighting COVID-19 Racial Disparities Can Reduce Support for Safety Precautions Among White U.S. Residents

Abstract: U.S. media has extensively covered racial disparities in COVID-19 infections and deaths. In two preregistered studies, we examined how the association between people of color and COVID-19 impacts White U.S. residents’ attitudes toward COVID-19 and people of color. Utilizing a correlational design (N = 498), we found that awareness of COVID-19 racial disparities predicted reduced fear of COVID-19 and race-related social distancing. Next, we manipulated exposure to information about COVID-19 racial disparitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Emerging research in a related area has found that merely informing members of dominant racial or ethnic groups (Whites) of racial disparities in COVID-19 infections and deaths has the potential to exacerbate, rather than reduce, such inequalities (Skinner-Dorkenoo et al, 2022). Such research suggests that making dominant-group members aware of racial bias and prejudice related to COVID-19 can reduce fear of a common threat as well as empathy—allowing COVID-19 to be perceived as a problem for out-groups yet not for the self or in-group.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Emerging research in a related area has found that merely informing members of dominant racial or ethnic groups (Whites) of racial disparities in COVID-19 infections and deaths has the potential to exacerbate, rather than reduce, such inequalities (Skinner-Dorkenoo et al, 2022). Such research suggests that making dominant-group members aware of racial bias and prejudice related to COVID-19 can reduce fear of a common threat as well as empathy—allowing COVID-19 to be perceived as a problem for out-groups yet not for the self or in-group.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…The latter approach may clarify a point that is not addressed in our analysis: although awareness separation may reduce disparities in severe disease-linked outcomes, this phenomenon is not necessarily equitable or desirable. In fact, if self-protection is associated with significant costs, already-vulnerable populations may suffer compounding costs as they balance self-protection against significant disease risk without adequate support from a broader community that does not share their risks (Atchison et al, 2021; Barrett et al, 2011; Jay et al, 2020; Skinner-Dorkenoo et al, 2022). Further, structural inequities often leave population subgroups that are vulnerable to larger, more severe outbreaks with reduced access to protective measures like health education, treatment, vaccination, and paid leave (Cardona et al, 2021; Christensen et al, 2020; Clouston et al, 2015; Dryhurst et al, 2020; Heymann et al, 2021; Poteat et al, 2020; Ridenhour et al, 2022; Simione & Gnagnarella, 2020; Williams & Cooper, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…67,68 A growing body of work suggests that knowledge of these inequities may result in increasing support for protective measures among those directly impacted by structural racism and other systems of oppression while simultaneously decreasing support among systematically advantaged groups whose relative position largely insulates them from COVID-19 harms. [67][68][69] In several studies and polls, Black and Latinx parents were less likely to have confidence that schools could reopen safely without additional protections and more likely to support school masking requirements. 67,68,70,71 In contrast, when randomized to receive information about pervasive racial/ethnic COVID-19 inequities, white individuals were less likely to report concern about COVID-19, empathy for those vulnerable to COVID-19, and less likely to support COVID-19 prevention policies.…”
Section: Discussionmentioning
confidence: 99%
“…67,68,70,71 In contrast, when randomized to receive information about pervasive racial/ethnic COVID-19 inequities, white individuals were less likely to report concern about COVID-19, empathy for those vulnerable to COVID-19, and less likely to support COVID-19 prevention policies. 69 Given vastly unequal environmental conditions shaping COVID-19 risk, universal school masking policies are an important measure for mitigating the impacts of structural racism and may be especially important in settings where other preventive measures such as upgraded ventilation/filtration may be more resource-and time-intensive to implement. School districts and policymakers should consider these inequitable impacts when making plans about masking policies for the upcoming school year.…”
Section: Discussionmentioning
confidence: 99%